Highly Active, Chemo‐ and Regioselective YbII and SmII Catalysts for the Hydrophosphination of Styrene with Phenylphosphine. Issue 16 (11th March 2015) - Basalov, Ivan V.; Dorcet, Vincent; Fukin, Georgy K.; Carpentier, Jean‐François; Sarazin, Yann; Trifonov, Alexander A.
Abstract Stable heteroleptic amido YbII and SmII complexes bearing aminoether–phenolate ligands and devoid of coordinated solvent have been structurally characterized. They afford highly active, chemoselective and, in the case of monoadditions, 100 % anti‐Markovnikov regiospecific catalysts (down to 0.04 mol % loading) for the hydrophosphination of styrene with PhPH2 under mild conditions.